Effects of Combined Application of Compost and Mineral Fertilizer on Soil Carbon and Nutrient Content, Yield, and Agronomic Nitrogen Use Efficiency in Maize-Potato Cropping Systems in Southern Ethiopia - Zeleke Asaye; Dong-Gill Kim; Fantaw Yimer; Katharina Prost; Oukula Obsa; Menfese Tadesse; Mersha Gebrehiwot; Nicolas Brüggemann (Land, 2022)
Low nutrient input and low soil fertility are limiting agricultural productivity in Ethiopia. The main objectives were therefore to evaluate the effects of combined compost and mineral fertilizer (MF) application on soil properties, yield, agronomic nitrogen use efficiency, and adoption of compost application in maize (Zey mays L.)—potato (Solanum tuberosum L.) cropping systems. Yield data were collected from 20 smallholders applying (i) compost and MF at a total rate of 110 kg N ha−1, with 6 Mg compost ha−1 + MF (6CF), 12 Mg compost ha−1 + MF (12CF), and 16 Mg compost ha−1 + MF (16CF; compost on a fresh weight basis), (ii) MF application of 108 kg N ha−1 (F), and (iii) zero fertilization. Soil from 0–20 and 20–40 cm depths was collected from 16 farms using compost and MF. Compost + MF treatments showed significantly lower soil bulk density and iron contents, while pH, electrical conductivity, and cation exchange capacity were higher compared to F treatments. The 6CF, 12CF, and 16CF showed 22, 43, and 54% higher maize grain yield and 8, 16, and 18% higher potato tuber yield compared to F, respectively. The scarcity of organic material was a major socioeconomic constraint for smallholders for producing and applying compost.